Improving Front Roll Ability With The Drill Method Through Guided Learning Strategies - John Yen Felix Pakpahan; Dodi Irwansyah; Basyarudin Acha (Jurnal Pendidikan Jasmani (JPJ), 2026)
Learning floor gymnastics, particularly forward rolls, still faces challenges due to low student skills, resulting in suboptimal learning outcomes. This study aims to improve the forward roll skills of class VII.1 students at SMP Negeri 7 Langsa using the drill method through a guided learning strategy. The study used a classroom action approach (CAR) with two cycles. The research subjects were 30 students selected using a total sampling technique. Data were collected through forward roll practice tests and observations, then analyzed descriptively quantitatively. The results showed an increase in learning completeness from 30% in the pre-cycle to 70% in the first cycle, and reached 93.33% in the second cycle. This increase confirmed that repeated practice with teacher guidance can improve technique, increase coordination, and foster student motivation. It was concluded that the drill method through a guided learning strategy is effective in improving forward roll skills and is worthy of being used as an alternative physical education learning strategy in schools.